Pseudorapidity distributions of charged hadrons in proton-lead collisions at root s(NN)=5:02 and 8.16 TeV - Sirunyan,AM; Tumasyan,A; Adam,W; Ambrogi,F; Asilar,E; Bergauer,T; Brandstetter,J; Brondolin,E; Dragicevic,M; Eroe,J; Flechl,M; Friedl,M; et al. (Journal of High Energy Physics, 2018)
The pseudorapidity distributions of charged hadrons in proton-lead collisionsat nucleon-nucleon center-of-mass energies √sNN = 5.02 and 8.16 TeV are presented.The measurements are based on data samples collected by the CMS experiment at theLHC. The number of primary charged hadrons produced in non-single-diffractive protonleadcollisions is determined in the pseudorapidity range |ηlab| < 2.4. The chargedhadronmultiplicity distributions are compared to the predictions from theoretical calculationsand Monte Carlo event generators. In the center-of-mass pseudorapidity range|ηcm| < 0.5, the average charged-hadron multiplicity densities hdNch/dηcmi |ηcm|< 0.5 are17.31 ± 0.01 (stat) ± 0.59 (syst) and 20.10 ± 0.01 (stat) ± 0.85(syst) at √sNN = 5.02 and8.16 TeV, respectively. The particle densities per participant nucleon are compared tosimilar measurements in proton-proton, proton-nucleus, and nucleus-nucleus collisions.